A study case on factors that affect the economic growth of tourism industry in Southeast Asia / Saunia Nazrin Mohd Sa’aid - Mohd Sa’aid, Saunia Nazrin (2015)
This study uses secondary data from 1995 until 2014 to analyze the pattern of the Gross Domestic Product (GDP) of tourism industry and the factors that influencing it. Economic studies focus on number of international arrivals, tourism receipts, capital investments, real effective exchange rates and employments. Apart from that, the other objective of this research is to determine the factors that influence the Gross Domestic Product (GDP) of tourism industry in Southeast countries which are Malaysia, Thailand and Singapore. There are several methods of analysis were used to analyze the data which are Panel Unit Root Test, Pooled Ordinary Least Square (OLS), Panel Regression Fixed Effect, normality test, autocorrelation and heteroscedasticity test. The result proved that there have a positive relationship between factors that influencing (ARV, CP, EMP, and REER) and GDP of tourism industry in Southeast Asia countries.